Oral Corrective Feedback Strategies and Learner Uptake in EFL Setting - Risna Saswati (Journal of English Language and Culture, 2021)
This study investigates the strategies of oral corrective feedback applied by senior teachers in EFL speaking classes. It is to shed light on whether those strategies used are effective to lead the repair uptake. Additionally, it is to find out the attempts done by the learners to repair their errors. This study applies a qualitative method that uses classroom observations as the technique for collecting the data. The data are taken from speaking classes taught by three senior teachers in three universities. The study reveals that the corrective feedback strategies of correct forms elicited were effective to lead to repair uptake. Those were elicitation, clarification request, repetition, and metalinguistic cue. Related to uptake, the learners attempted to achieve well-formed sentences by the process of Needs Repair to Repair uptake. It involved the same errors and acknowledgment for Needs Repair and incorporation, repetition, and self-repair for repair uptake. It is recommended that teachers apply the correct form elicited corrective feedback strategies to correct learners’ erroneous forms and provide the uptake since it is the learning process.Keywords: Oral Corrective Feedback strategies, Learners’ uptake, Repair, Needs Repair